Strategic Management of Islamic Boarding School Leader: Improving Quality of Graduates at Khairul Ummah Air Molek - Asmariani, Asmariani; Syukri, Ahmad; Hakim, Lukman (PT. Riset Press International, 2025)
Khairul Ummah Air Molek Islamic Boarding School (PPKU) has a distinctive feature: collegial collective leadership. This can be seen when decision-making is not decided by the Head of the Boarding School or the Kiyai alone but with the Education quality supervisor and internal quality assurance. This study uses a qualitative descriptive approach through the perspective of Education science with participatory observation to describe, illustrate, explore, and describe the strategic management of Islamic boarding school leaders in improving the quality of Islamic Education. The purpose of this study is so that readers can learn about the strategic management of Islamic boarding school leaders in improving the quality of graduates at PPKU Air Molek comprehensively from various sides. The results of this study reveal that the Formulation of strategic management of PPKU Air Molek leaders has been running well through the Boarding School musrembang (development plan meeting), which can be seen in the preparation of the vision, mission, goals, and SWOT analysis. The implementation of strategic management has opened 5 branches in Riau province. Strategic management evaluation is carried out by management in yearly, semesterly, quarterly, and monthly evaluation stages based on special events and criteria. Meanwhile, the improvement of Education Quality at PPKU has a significant improvement in Education Quality, firstly, the increasing public interest; secondly, the acceptance of graduates in various well-known schools and universities; and thirdly, all of the Education institutions in PPKU have accreditation.